2013
DOI: 10.1371/journal.pntd.0002461
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neutrophil-Secreted Myeloid Related Proteins 8 and 14 (MRP 8/14) on Leishmaniasis Progression

Abstract: The myeloid-related proteins (MRPs) 8/14 are small proteins mainly produced by neutrophils, which have been reported to induce NO production in macrophages. On the other hand, Leishmania survives and multiplies within phagocytes by inactivating several of their microbicidal functions. Whereas MRPs are rapidly released during the innate immune response, their role in the regulation of Leishmaniasis is still unknown. In vitro experiments revealed that Leishmania infection alters MRP-induced signaling, leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…As shown in Figure , concentrations over 100 µg/mL after 24 h had significant cytotoxic impact on cell viability. Cell growth inhibitory effect of CP against various cells ranging from normal fibroblast cells to several tumor cells has been demonstrated by different research groups (Contreras et al, ; Yui et al, ; Zali et al, ). Following this observation we performed other experiments to elucidate the possible mechanism(s) by which CP mediates LNCaP cell viability inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure , concentrations over 100 µg/mL after 24 h had significant cytotoxic impact on cell viability. Cell growth inhibitory effect of CP against various cells ranging from normal fibroblast cells to several tumor cells has been demonstrated by different research groups (Contreras et al, ; Yui et al, ; Zali et al, ). Following this observation we performed other experiments to elucidate the possible mechanism(s) by which CP mediates LNCaP cell viability inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Mrp8 and Mrp14 (calprotectin) have been identified as biomarkers of the aging process [3], but while their pro-inflammatory activity has been documented in young mice under acute stress [1623], their contributions to chronic inflammation at older ages remains unclear. This study compared Mrp14-KO and WT mice at young and old ages but obtained no evidence that age-related inflammation is blunted by Mrp8/Mrp14 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have identified Mrp14-KO phenotypes only in the context of acute pro-inflammatory stimuli [1623], which has fostered the view that KO and WT mice differ little under standard physiological conditions [16, 17]. This conflicts with our observations, however, since we identified 215 genes differentially expressed between livers from KO and WT mice at 5 months of age, in the absence of any stressful or pro-inflammatory conditions (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations